6 - Le profil du responsable du personnel au Sénégal : le discours et la réalité: 10.4314/ad.v25i1.22113 - Tidjani, Bassirou (Africa Development, 2000)
This study draws the profile of human resource development managers to identify some of their practices in Senegal. It explores the results of a study of hundred enterprises from various sectors and of diverse sizes of the country's economy. The findings reveal that although human resource managers participate in corporate decision-making, they have had no previous training in the field, have acquired the position after having occupied other positions in the company or enterprise and devote most of their time running day-to-day activities rather than on plans to develop the capacity of their personnel.